PELATIHAN SWOT BALANCED SCORECARD UNTUK PENGUKURAN KINERJA INDUSTRI BRIKET ARANG - EKADJAJA, MARGARITA; Djaja, Tara Clarissa (Jurnal Bakti Masyarakat Indonesia, 2022)
The PKM team collaborated with Trinity Charcoal Indonesia which is a producer of charcoal briquettes in measuring performance using the SWOT balanced scorecard method. The background of implementation of PKM activities is the partner's expectation to increase profits to grow the company, because the increase in sales achieved by partner is not followed by the expected increase in profits. PKM activities help partners take advantage of their strengths, weaknesses, opportunities, and threats in determining business strategies so as to create a balance between various perspectives and thus partners can focus more on the target market to be served. The initial stage of implementing PKM was the team conducted a webinar using the Zoom application with the topic of using the balanced scorecard for performance measurement. The success of the webinar implementation is evaluated through the partner's ability to create a balanced scorecard related to its business activities. The next step is the PKM team helps partners create a SWOT matrix. Information and data collection such as financial plans, marketing plans, operation plans, quality improvement programs, and customer analysis related to partners is carried out by interviewing techniques through the WhatsApp application. Meanwhile, data collection of information related to partner industries is carried out through a questionnaire technique distributed online through the google form. Based on the results of the measurement of the total score of the SWOT matrix, partners are in quadrant 1 position, which means partners can take advantage of the strengths and opportunities of the products they produce. The results of the SWOT analysis prioritize partners' work plans in order to improve their performance. The mandatory outputs for the implementation of PKM are published through the SERINA and Tarumanagara University online mass media. ABSTRAK Tim PKM bekerjasama dengan Trinity Charcoal Indonesia yang merupakan produsen briket arang dalam mengukur kinerja menggunakan metode SWOT balanced scorecard. Hal yang mendasari pelaksanaan kegiatan PKM adalah mitra berkeinginan meningkatkan keuntungan sehingga perusahaannya dapat berkembang, namun peningkatan penjualan produk mitra tidak diikuti dengan peningkatan keuntungan yang diharapkan. Kegiatan PKM membantu mitra memanfaatkan strengths, weaknesses, opportunities, dan threats yang dimiliki dalam penentuan strategi bisnis sehingga tercipta keseimbangan antar berbagai perspektif dan mitra dapat lebih memfokuskan target market yang akan dilayani. Tahap awal pelaksanaan PKM adalah tim melaksanakan webinar menggunakan aplikasi Zoom dengan topik pemanfaatan balanced scorecard untuk pengukuran kinerja. Keberhasilan pelaksanaan webinar dievaluasi melalui kemampuan mitra dalam membuat balanced scorecard terkait dengan kegiatan usahanya. Tahap selanjutnya, tim PKM membantu mitra membuat matriks SWOT. Pengumpulan data informasi seperti mengenai rencana keuangan, rencana pemasaran, rencana pengoperasian, program peningkatan kualitas, dan analisa pelanggan terkait dengan mitra dilakukan dengan teknik wawancara melalui aplikasi WhatsApp. Sedangkan pengumpulan data informasi terkait dengan industri mitra dilakukan melalui teknik kuesioner yang disebar secara online melalui google form. Berdasarkan hasil pengukuran total skor matriks SWOT, mitra berada pada posisi kuadran 1 yang berarti mitra dapat memanfaatkan kekuatan dan peluang dari produk yang dihasilkannya. Hasil analisa SWOT tersebut memprioritaskan rencana kerja mitra agar dapat meningkatkan kinerjanya. Luaran wajib pelaksanaan PKM dipublikasikan melalui SERINA sebagai luaran wajib dan media massa online Universitas Tarumanagara sebagai luaran tambahan.